(untitled) (Journal of the College of Basic Education, 2024)
This study shows that neglecting creative abilities leads to the backwardness of societies, which necessitates the need to develop and flourish modern society by adopting original ideas to solve problems. Accordingly, the study aimed to examine the effect of using Triffinger’s model of developmental organization on the production of creative ideas among students of the Institute of Arts in the field of design techniques, especially in interior design. The model was applied through teaching plans designed according to the model and compared with traditional methods on a sample of students to measure the effect. The research sample consisted of students of the Institute of Fine Arts, where they were carefully selected to ensure accurate representation of the academic community. The researcher adopted the experimental design with two equivalent groups to compare the effect before and after. The results showed significant differences in the creative performance of female students who studied according to the Treffinger model compared to the traditional method, which highlights the effectiveness of the model in enhancing creative abilities. Accordingly, the researcher recommended the necessity of adopting this model in the educational process in general and in fine arts institutes in particular, and suggested conducting more applied studies to generalize the benefits of this model.